World Bank Group Approaches to Mobilize Private Capital for Development : An Independent Evaluation - World Bank (World Bank, Washington, DC, 2021)
To achieve the Sustainable Development Goals (SDGs) by 2030, development institutions will need to leverage an unprecedented amount of private sector capital. This is more pressing in the current context as COVID-19 recoveries will require mobilizing both public and private sources in the short to medium term. Consequently, private capital mobilization (PCM) has become a World Bank Group priority, with efforts being deployed across all Bank Group institutions, under the context of the Maximizing Finance for Development (MFD) strategy. This evaluation offers IEG’s first systematic assessment of the Bank Group’s approaches to mobilize private capital to achieve development outcomes by engaging with investors and project sponsors. The evaluation finds Bank Group PCM approaches to have been relevant to both country and corporate clients, although partially meeting investor’s priorities and expectations. The evaluation finds that PCM approaches are mostly effective in mobilizing private capital and points to the untapped PCM potential that still exists even in low-income and lower-middle income countries. The evaluation also highlights important gaps: IBRD PCM targets have not cascaded to Regional units and Global Practices (GPs), and IFC PCM approaches are not consistently aligned with investors’ risk appetites. The evaluation identifies three near-term actions that can enhance the ability of the Bank Group to mobilize private capital and thus improve the probability of meeting corporate targets and improving outcomes: (i) To meet the 2030 PCM targets, prioritize client countries for PCM approaches, with corresponding targets cascading to the Regional units and GPs (IBRD); (ii) Expand PCM platforms, guarantees, and disaster risk management products commensurate with project pipeline development (World Bank Group); and (iii) Develop new PCM products and improve product alignment with the needs of new investor groups and partners (IFC and MIGA).